2013
DOI: 10.1371/journal.pone.0063643
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Cognition, Proton MR Spectroscopy and Synaptic and Neuronal Pathology in Aging Wild-type and AβPPswe-PS1dE9 Mice

Abstract: Proton magnetic resonance spectroscopy (1H MRS) is a valuable tool in Alzheimer’s disease research, investigating the functional integrity of the brainThe present longitudinal study set out to characterize the neurochemical profile of the hippocampus, measured by single voxel 1H MRS at 7 Tesla, in the brains of AβPPSswe-PS1dE9 and wild-type mice at 8 and 12 months of age. Furthermore, we wanted to determine whether alterations in hippocampal metabolite levels coincided with behavioral changes, cognitive declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 121 publications
(136 reference statements)
9
22
1
Order By: Relevance
“…In agreement with previous results from our lab [58], [76], 11-month-old AβPP-PS1 mice displayed increased activity and anxiety-related behavior, and decreased explorative behavior in the open field as compared to age-matched wild-type mice. Hyperactivity and decreased explorative behavior are specific characteristics of many AβPP transgenic mice [77][79] and may be explained as a result of elevated anxiety levels [80], [81].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous results from our lab [58], [76], 11-month-old AβPP-PS1 mice displayed increased activity and anxiety-related behavior, and decreased explorative behavior in the open field as compared to age-matched wild-type mice. Hyperactivity and decreased explorative behavior are specific characteristics of many AβPP transgenic mice [77][79] and may be explained as a result of elevated anxiety levels [80], [81].…”
Section: Discussionsupporting
confidence: 93%
“…In line with our previous findings [76], AβPP-PS1 and wild-type mice showed a similar decrease in escape latency during training in the reversal MWM. The reversal task requires selective memory retrieval of the newly learned location of the platform, and contains therefore an extra episodic component [60], [103].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both FAD mice had the same metabolite profile in the DG as their wild type controls. A previous study investigating APPswe/PS1 ΔE9 mice by 1 H-MRS also found no variations in hippocampal metabolite levels at 8 months of age [24]. 3xTg-AD mice had elevated mI, glutamate, and glutamine in the cortex and no alterations in the SVZ.…”
Section: Discussionmentioning
confidence: 81%
“…myo-Inositol is a sugar alcohol that is thought to be a marker for osmotic stress, astrogliosis and microglial activation (Govindaraju et al 2000), and an increase in cerebral myo-inositol levels is therefore associated with inflammatory processes. Significant differences in hippocampal myo-inositol/glycine concentrations between 12-month-old wild-type and AβPP-PS1 mice were not observed, but correlation analysis revealed a positive correlation between the levels of Aβ-40 and Aβ-42 aggregates and myo-inositol/glycine levels in the AβPP-PS1 animals, suggesting the possible involvement of Aβ in the inflammatory process (Jansen et al 2013). Furthermore, disturbances of several other metabolites have been found in AD patients, although the reports are inconsistent.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%